2020
DOI: 10.2217/epi-2020-0101
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis Integrating Metabolomics of m 6 A RNA Microarray in Intervertebral Disc Degeneration

Abstract: Aim: To explore the potential functions and mechanism of N6.methyladenosine (m6A) abnormality of RNAs in nucleus pulposus from the intervertebral disc degeneration (IDD). Materials & methods: We performed rat model, m6A epitranscriptomic microarray, bioinformatics analysis and metabolomics. Results: In IDD, most of the differentially methylated RNAs showed a significant demethylation situation. The competing endogenous RNA network LOC1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 88 publications
1
25
0
Order By: Relevance
“…In addition, marker metabolites in the late stage of degeneration were mainly involved in sugar metabolism pathways such as amino sugar and nucleotide sugar metabolism, proteoglycan structural metabolism, and tricarboxylic acid (TCA) cycle; protein metabolism pathways such as cysteine and methionine metabolism and serine and threonine metabolism; and small molecule metabolism including niacin and nicotinamide metabolism and PGI2 metabolism. Consistent with the findings on metabolic pathways, the main biological processes involved in rat IDD were energy metabolism [32], biological oxidation [33], and structural protein synthesis and decomposition [34]. Gly-Ser-Thr metabolic pathways are involved in biotransformation and metabolic activities during degeneration [35].…”
Section: Oxidative Medicine and Cellular Longevitysupporting
confidence: 78%
“…In addition, marker metabolites in the late stage of degeneration were mainly involved in sugar metabolism pathways such as amino sugar and nucleotide sugar metabolism, proteoglycan structural metabolism, and tricarboxylic acid (TCA) cycle; protein metabolism pathways such as cysteine and methionine metabolism and serine and threonine metabolism; and small molecule metabolism including niacin and nicotinamide metabolism and PGI2 metabolism. Consistent with the findings on metabolic pathways, the main biological processes involved in rat IDD were energy metabolism [32], biological oxidation [33], and structural protein synthesis and decomposition [34]. Gly-Ser-Thr metabolic pathways are involved in biotransformation and metabolic activities during degeneration [35].…”
Section: Oxidative Medicine and Cellular Longevitysupporting
confidence: 78%
“…Meanwhile, the changes of m 6 A modification of lncRNAs distribution were analyzed by exogenous stimulation. The profiles of m 6 A modification of lncRNAs in mammals were identified in recent years, such as mouse, rat and human [43][44][45][46]. Meanwhile, large intergenic noncoding RNAs (lincRNAs) which are one class of lncRNAs transcribed from intergenic regions are defined [47].. Key roles for lincRNAs in certain biological processes are starting to emerge.…”
Section: Discussionmentioning
confidence: 99%
“…The pro les of m 6 A modi cation of lncRNAs in mammals were identi ed in recent years, such as mouse, rat and human [32][33][34][35]. Dominissini et al suggested that m 6 A in exonic regions was preferentially found in longer exons in human and mouse [36].…”
Section: Discussionmentioning
confidence: 99%